Testing the effects of player matching in basketball matches and small-sided game training scenarios based on the relative age effect: A 6-month study on physical performance and skill adaptations - Wei, L.; Zheng, Y., Li, M.; Dai, S. H. (Journal of Sports Science & Medicine, 2025)
Identifying strategies to mitigate the impact of the Relative Age Effect (RAE) on the development of youth basketball players is crucial. This study aimed to compare two methods of player grouping during competitive small-sided games and match scenarios in training sessions, focusing on their impact on physical performance and technical skill development: mixed birthdate quartiles (CON) versus structured grouping based on birthdate quartiles (BG) over a 6-month period. A randomized controlled trial was conducted with forty-one youth basketball players (age: 12.9 ± 0.7 years) at a trained/developmental level. Throughout the study, participants in the BG group (n = 20) were assigned to small-sided games or match competition scenarios based on their birthdate quartiles, while those in the CON group (n = 21) were grouped with players from mixed quartiles. Players were evaluated at baseline and after the 6-month period for physical performance using countermovement jump (CMJ), change-of-direction (COD), and aerobic capacity (YYIRT). Additionally, they were assessed for technical skills in shooting, passing, and dribbling tests. Comparisons were made based on both birthdate quartiles (quartiles q1-2 relatively older, and q3-4 relatively younger players) and group. After 6 months, the CONq3q4 covered a shorter YYIRT distance than the CONq1q2 group (p = 0.040), achieved a lower CMJ height than both the CONq1q2 (p = 0.024) and BGq1q2 groups (p = 0.019), and had a greater COD deficit than the CONq1q2 group (p = 0.046). Additionally, the CONq3q4 group had longer dribbling times than the CONq1q2 (p = 0.002), BGq1q2 (p = 0.004), and BGq3q4 (p = 0.009) groups. In skill assessments, the CONq3q4 group scored lower in passing than both the CONq1q2 (p = 0.015) and BGq1q2 groups (p = 0.025), and scored lower in shooting compared to the CONq1q2 (p = 0.019), BGq1q2 (p = 0.003), and BGq3q4 (p = 0.003) groups. Grouping youth basketball players based on birthdate quartiles during training can mitigate the relative age effect, promoting more equitable physical and technical development by reducing age-related biases. However, these conclusions are limited by the study's duration and require further research over the long term.